2008
DOI: 10.1097/ftd.0b013e318186e08e
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Antiretroviral Drug Concentrations in Breast Milk: Validation of a Liquid Chromatography-Tandem Mass Spectrometric Method for the Determination of 7 Anti-Human Immunodeficiency Virus Medications

Abstract: Studying the pharmacokinetics of antiretroviral drugs in breast milk has important implications for the health of both the mother and the infant, particularly in resource-poor countries. Breast milk is a highly complex biological matrix, yet it is necessary to develop and validate methods in this matrix, which simultaneously measure multiple analytes, as women may be taking any number of drug combinations to combat human immunodeficiency virus infection. Here, we report a novel extraction method coupled to hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 13 publications
4
27
0
Order By: Relevance
“…Our findings regarding the breast milk/plasma ratio for nelfinavir are consistent with those of other studies, which found this ratio to be 0.06 to 0.24 (4,8). Studies of nelfinavir have typically calculated maternal breast milk/plasma ratios, which may underestimate the actual proportion of drug transferred to breast milk, and pharmacokinetic studies using a ratio calculated from the area under the curve may better characterize the proportion of drug transferred (1).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our findings regarding the breast milk/plasma ratio for nelfinavir are consistent with those of other studies, which found this ratio to be 0.06 to 0.24 (4,8). Studies of nelfinavir have typically calculated maternal breast milk/plasma ratios, which may underestimate the actual proportion of drug transferred to breast milk, and pharmacokinetic studies using a ratio calculated from the area under the curve may better characterize the proportion of drug transferred (1).…”
Section: Discussionsupporting
confidence: 81%
“…Antiretrovirals cross from maternal plasma to breast milk and from breast milk to the infant in different concentrations (4,5,7,8,9,10). The Kisumu Breastfeeding study (KiBS) was a phase IIb open-label single-arm PMTCT trial of maternal triple-antiretroviral regimens administered from 34 weeks' gestation to 6 months postpartum while infants exclusively breast-fed.…”
mentioning
confidence: 99%
“…LPV and RTV breastmilk concentrations were ~11% that of concentrations in mothers’ plasma, but all infants had undetectable LPV and RTV plasma concentrations at all three time points, consistent with our data showing negligible absorption or transfer of these drugs during breastfeeding. In another study, no detectable levels of LPV or RTV were seen in milk samples from 60 HIV-infected mothers on LPV/r-based regimens 29 . A recent study of 66 HIV-infected women on various combination antiretroviral regimens in Malawi 30 showed that breastmilk penetration for LPV was lower than that of other antiretrovirals, although higher breastmilk concentrations of LPV and RTV were observed in mothers at delivery than at later time points.…”
Section: Discussionmentioning
confidence: 93%
“…In that study, d4T concentrations were undetectable (<5 ng/ml) in eight serum samples collected from four infants who were exposed to maternally-administered d4T [16]. In another study, d4T was detected in breast milk from 2 women [17]. …”
Section: Discussionmentioning
confidence: 99%